IMPLEMENTASI METODE CPM (CRITICAL PATH METHOD) MODEL AOA (ACTIVITY ON ARCH) PADA APLIKASI PENJADWALAN PROYEK - Bambang Wahyudi; Dadang Hamdani; Gigin Ginanjar (NUANSA INFORMATIKA, 2011)
Planning and scheduling of project activities are very important because they can be used as the base for implementing the project in order to finish the projects by the optimal time. The level of the estimated project duration is determined by the level of the estimated duration of each activity in the project. Therefore, analysis of the optimization project duration is needed to know how long a project is completed and for the possibility of accelerating project duration. One popular technique in scheduling is a network planning. Network planning is one of the models that is widely used in the project implementation, which can provide information about the activities in the network diagram. Critical path method with activity on arch model is one of the techniques in network planning. Critical path is a path of critical activities concerning in project scheduling, because the project is late or does not depend on the activities in the critical path. However, in determining the critical path, it is always found the complicated calculations, so in this paper the author will make a software using the critical path method with activity on arch model which will help simplifying the calculation of the critical path and to build network diagram. By using the software, it is hoped that it can help analizing project scheduling. So that it becomes easier for calculating the critical activities of the project and we can see the duration of activities, such as result of forward pass and backward pass. This software is capable to present a network diagram of the project.